Experimental Evidence Shows the Importance of Behavioural Plasticity and Body Size under Competition in Waterfowl - Zhang, Yong; Prins, Herbert H. T.; Versluijs, Martijn; Wessels, Rick; Cao, Lei; de Boer, Willem Frederik (PloS one, 2016)
When differently sized species feed on the same resources, interference competition may occur, which may negatively affect their food intake rate. It is expected that competition between species also alters behaviour and feeding patch selection. To assess these changes in behaviour and patch selection, we applied an experimental approach using captive birds of three differently sized Anatidae species: wigeon (Anas penelope) (~600 g), swan goose (Anser cygnoides) (~2700 g) and bean goose (Anser fabalis) (~3200 g). We quantified the functional response for each species and then recorded their behaviour and patch selection with and without potential competitors, using different species combinations. Our results showed that all three species acquired the highest nitrogen intake at relatively tall swards (6, 9 cm) when foraging in single species flocks in the functional response experiment. Goose species were offered foraging patches differing in sward height with and without competitors, and we tested for the effect of competition on foraging behaviour. The mean percentage of time spent feeding and being vigilant did not change under competition for all species. However, all species utilized strategies that increased their peck rate on patches across different sward heights, resulting in the same instantaneous and nitrogen intake rate. Our results suggest that variation in peck rate over different swards height permits Anatidae herbivores to compensate for the loss of intake under competition, illustrating the importance of behavioural plasticity in heterogeneous environments when competing with other species for resources.